2018
DOI: 10.1021/acs.jpclett.8b02793
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of O–O Bond Formation in the Final Metastable S3 State of Nature’s Water Oxidizing Complex Implying a Novel Mechanism of Water Oxidation

Abstract: A novel mechanism for the final stages of Nature's photosynthetic water oxidation to molecular oxygen is proposed. This is based on a comparison of experimental and broken symmetry density functional theory (BS-DFT) calculated geometries and magnetic resonance properties of water oxidising complex models in the final metastable oxidation state, S 3. We show that peroxo models of the S 3 state are in vastly superior agreement with the current experimental structural determinations compared with oxohydroxo model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 45 publications
9
86
1
Order By: Relevance
“…These two forms were previously discussed by Krewald et al [30], who had concluded that the presence or absence of the O6H-O5 hydrogen bond has only a small energetic effect and does not significantly perturb the magnetic and spectroscopic properties of the cluster [30]. The same conclusions are reached by Corry and O'Malley [50]. Note that the O5-O6 distance is ca.…”
Section: Peroxo/superoxo Models For the S 3 Statesupporting
confidence: 64%
See 4 more Smart Citations
“…These two forms were previously discussed by Krewald et al [30], who had concluded that the presence or absence of the O6H-O5 hydrogen bond has only a small energetic effect and does not significantly perturb the magnetic and spectroscopic properties of the cluster [30]. The same conclusions are reached by Corry and O'Malley [50]. Note that the O5-O6 distance is ca.…”
Section: Peroxo/superoxo Models For the S 3 Statesupporting
confidence: 64%
“…The proton of the OH group may either point towards the O5 bridge or away from it, establishing instead a hydrogen bond with another acceptor group, for example the carboxylate of Glu189. In either case, the distance between O5 and O6 is computed at ~2.4-2.6 Å [30,[48][49][50]68]. According to DFT calculations these alternative hydrogen-bonding patterns lie too close to be reliably distinguishable energetically [30].…”
Section: Spectroscopy-consistent Computational Models For the S 3 Statementioning
confidence: 98%
See 3 more Smart Citations